1992
DOI: 10.1159/000243843
|View full text |Cite
|
Sign up to set email alerts
|

Lung Mechanics (FRC and Static Pressure-Volume Diagram) after Endotracheal Surfactant Instillation: Preliminary Observations

Abstract: Preliminary measurements of functional residual capacity (FRC) with the sulphurhexafluoride technique and static pressure volume diagrams were performed in newborn infants with respiratory distress syndrome receiving endotracheal instillation of natural porcine surfactant (Curosurf, 100 or 200 mg/kg). Within the first hour after surfactant treatment there was an increase in FRC and distensibility of the lungs persisting for 24-48 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
5
7
0
1
Order By: Relevance
“…The results from the present study regarding FRC and CRS in infants with severe RDS are comparable to those reported previously [11,16,19,20,24,39]. Our data confirm that infants with severe RDS have non-compliant [18,43], low volume lungs [24,26,32,43].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results from the present study regarding FRC and CRS in infants with severe RDS are comparable to those reported previously [11,16,19,20,24,39]. Our data confirm that infants with severe RDS have non-compliant [18,43], low volume lungs [24,26,32,43].…”
Section: Discussionsupporting
confidence: 91%
“…Although some recruitment of new alveoli probably may occur, we suggest that stabilisation of alveoli already being ventilated contributed mainly to FRC response immediately after surfactant instillation with the result that compliance remained unchanged or decreased. When measurements were repeated during the first days after surfactant treatment, compliance was observed to increase in this and also other studies [6,16,38,39], probably as a result of effective alveolar recruitment.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…While some animal studies suggest pressure-volume curves may be significantly improved, 44 improvement in compliance in preterm lambs treated with synthetic surfactant is small. 45 An increase in functional residual capacity (FRC) and distensibility of the lungs is reported within 1 hr of treatment in babies treated with some 46 but not other protein-containing surfactants. 47 Although babies treated with bovine surfactant have a more rapid improvement in FRC and lung compliance than babies treated with synthetic surfactant, 48 babies treated with synthetic surfactant have improved lung mechanics by 24 hr of age.…”
Section: Discussionmentioning
confidence: 99%